Barrier free campus landscape for students with disabilities - Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati (Asian Academic Research Journal of Multidisciplinary, 2015)
This paper discusses the theoretical aspects of disability and its relationship to campus planning. It presents the theoretical frameworks consist of the definition of disability and people with disabilities (PwDs); types of disabilities in built environment which cover issues and challenges faced by disabled peoples; outdoor spaces of campus planning and outdoor campus environment from the aspects of landscape design. This paper focuses on the barrier free campus landscape design in campus planning and reviews the needs of Student with Disabilities (SwDs) as part of PwDs in terms of their accessibility, safety, usability, and integrated design, in order to create a barrier free campus environment. The paper provides a platform to discover the needs of the disabled students, especially in the campus environment, based on the type of disabilities.